If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(c + -3) + -2 = 2(c + -1) + 3(c + -2) Reorder the terms: -4(-3 + c) + -2 = 2(c + -1) + 3(c + -2) (-3 * -4 + c * -4) + -2 = 2(c + -1) + 3(c + -2) (12 + -4c) + -2 = 2(c + -1) + 3(c + -2) Reorder the terms: 12 + -2 + -4c = 2(c + -1) + 3(c + -2) Combine like terms: 12 + -2 = 10 10 + -4c = 2(c + -1) + 3(c + -2) Reorder the terms: 10 + -4c = 2(-1 + c) + 3(c + -2) 10 + -4c = (-1 * 2 + c * 2) + 3(c + -2) 10 + -4c = (-2 + 2c) + 3(c + -2) Reorder the terms: 10 + -4c = -2 + 2c + 3(-2 + c) 10 + -4c = -2 + 2c + (-2 * 3 + c * 3) 10 + -4c = -2 + 2c + (-6 + 3c) Reorder the terms: 10 + -4c = -2 + -6 + 2c + 3c Combine like terms: -2 + -6 = -8 10 + -4c = -8 + 2c + 3c Combine like terms: 2c + 3c = 5c 10 + -4c = -8 + 5c Solving 10 + -4c = -8 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. 10 + -4c + -5c = -8 + 5c + -5c Combine like terms: -4c + -5c = -9c 10 + -9c = -8 + 5c + -5c Combine like terms: 5c + -5c = 0 10 + -9c = -8 + 0 10 + -9c = -8 Add '-10' to each side of the equation. 10 + -10 + -9c = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -9c = -8 + -10 -9c = -8 + -10 Combine like terms: -8 + -10 = -18 -9c = -18 Divide each side by '-9'. c = 2 Simplifying c = 2
| 12x-14y+3z=13 | | 4u-10u= | | 5v-4+2+7v= | | 31b-777= | | -8+6x+3x+4= | | 4.4=-6.5h+36.9 | | 58=-22+10x | | -7p+p=-4 | | 2e^2+12e-22= | | -5u+2+5u= | | W+2w+w+w= | | 4x^3-16x+2=0 | | t-2.89=915 | | -8x+2(x+2)=-26 | | -11+-5= | | 7n+5-5n-6= | | -3(2x-10)=-30 | | 4x-5y=-45 | | 4x=2y+10 | | -3n+10+n+9= | | 8x-7y=-63 | | 19=6d+1 | | 3r^27=0 | | 6g+24=72 | | 6x+5-1= | | 81xy-16x=36xy | | 10v-8+5v-6= | | 9x+40+4y+8=180 | | 19p+14=89-6p | | 7+3(-8x-4)=11 | | (x+15)+(x+5)+40=180 | | -5+5t=-20 |